2000
DOI: 10.1007/s001340051281
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure in the ICU: risk factors and outcome evaluated by the SOFA score

Abstract: In ICU patients, the most important risk factors for ARF or mortality from ARF are often present on admission. During the ICU stay, other organ failures (especially cardiovascular) are important risk factors. Oliguric ARF was an independent risk factor for ICU mortality, and infection increased the contribution to mortality by other factors. The severity of circulatory shock was the most important factor influencing outcome in ARF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
399
4
24

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 657 publications
(441 citation statements)
references
References 26 publications
14
399
4
24
Order By: Relevance
“…The studies show an association of a determined co-morbidity that may or may not affect the appearance of ARF in ICU (8,11,17) . In this study, the restrictive factor located was the small number of comorbidities that, when grouped, did not allow to identify them as a risk factor to ARF.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The studies show an association of a determined co-morbidity that may or may not affect the appearance of ARF in ICU (8,11,17) . In this study, the restrictive factor located was the small number of comorbidities that, when grouped, did not allow to identify them as a risk factor to ARF.…”
Section: Discussionmentioning
confidence: 89%
“…The ARF is defined, in most studies, as when there is elevation in the creatinine level between 1.3 mg/dl and 5.0 mg/dl, or when there is a need for dialysis treatment (8)(9)(12)(13)(14) . In this study, it was considered as serum creatinine levels greater than 1.5 mg/dl (11)(12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the previous decades, the component of AKI had been proposed instead of the WRF, and AKI has also been reported to affect the outcome of patients admitted to ICUs 29, 30, 31. The RIFLE criteria have been established as the standard method for evaluating AKI in intensive care patients 5, 6.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] The high mortality rate of these pathologies, especially in ICU, brings out the need for attention for this disease. [1][2][3][4][5][6][7] Studies on chronic kidney diseases have shown the importance of ethnical, 8 environmental, 9,10 socioeconomical, [11][12][13][14][15] and psychic factors, modulating the disease, its complications and progonosis. 16 Many investigations have demonstrated that chronic stress conditions are associated with allostatic overload, 17,18 that is, the attempt of the body to find stability through stressful change, thus leading to changes in cortisol and insulin levels, in the hypothalamo-hypophyseal axis (HPA), kinins, and other proinflammatory elements, among other homeostatic changes.…”
Section: Introductionmentioning
confidence: 99%